Capacity building of NARES and private sector in the deployment of Rice GAPfinder for Sustainable Rice Platform (SRP) standards implementation RiceAdvice Lite (RAL VAT) plots and data collected in Sikasso in Mali - Ahouanton, K.; Dossou-Yovo, E.R. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report provides an overview of the training activity conducted in August 2024 under the AICCRA project to support the implementation of the Sustainable Rice Platform (SRP) standards in rice-based systems in Mali. The training focused on the use of the Rice GAPfinder tool, designed by AfricaRice, to help partners from the Institut d'Économie Rurale (IER) assess and monitor sustainable rice practices in farmers' fields. In total, 19 staff from IER were trained. In addition to the training, backstopping was provided to IER staff in the deployment of the SRP tool to farmers. Field visits were conducted to monitor the RiceAdvice Lite validation trials (RAL VAT) and collect relevant data. Participants gained hands-on experience in using the SRP tool for benchmarking rice production standards and monitoring trial plots. The report outlines the key activities, challenges, and next steps, which include further monitoring and data collection to ensure the success of the validation trials and the effective implementation of SRP standards.